Pelayanan Kartu Tanda Penduduk Elektonik (E-Ktp) Oleh Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Indragiri Hulu - Nurzila, Nurzila; Abdul Sadad (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The government as a public service provider is needed by the community, which must be responsible and continue to strive to provide the best service in order to improve public services. Law Number 25 of 2009 concerning Public Services is a reference for all public service agencies in providing quality services. Quality public services provided by the government to the community have a very important role in determining the success and sustainable satisfaction of the community. Community satisfaction is a measure of the success of public services provided by public service providers. The purpose of this study is to describe the implementation of the Electronic Identity Card (e-KTP) service by the Department of Population and Civil Registration of Indragiri Hulu Regency and to analyze or identify the inhibiting factors in the implementation of the Electronic Identity Card (e-KTP) service by the Department of Population and Civil Registration Indragiri Hulu Regency. This study uses the Pasuraman theory (Makmur & Thoha, 2017) which consists of: Tangible (direct evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee), and Empathy (attention). The research method used is qualitative with a phenomenological approach, and the data sources used are primary data and secondary data, with data collection techniques namely observation, interviews, literature review, and documentation. The results of this study indicate that the service of Electronic Identity Cards (e-KTP) by the Department of Population and Civil Registration of Indragiri Hulu Regency from the aspects of tangible, reliability, responsiveness, assurance, and empathy has not been implemented properly. In addition, employees who work at the Department of Population and Civil Registration of Indragiri Hulu Regency have not been able to provide services in accordance with the expectations and desires of the community.